The Theology of Paul's Letter to the Romans - Haacker, Klaus (New York Cambridge University Press, 2003)
Klaus Haacker, a respected expert on Paul's writings, presents a compelling introduction to the theology of the Letter to the Romans. Professor Haacker focuses on the themes of righteousness, suffering and hope and the mystery of Israel in the age of th
Keywords: Bible. -- Romans -- Theology. Bible. -- New Testament. -- Romains -- Théologie. RELIGION -- Biblical Studies -- New Testament